2010
DOI: 10.1167/iovs.10-5503
|View full text |Cite
|
Sign up to set email alerts
|

CT Based Three-Dimensional Measurement of Orbit and Eye Anthropometry

Abstract: The comprehensive set of measurements collected in this study provides three-dimensional information on orbit geometry, as well as placement of the eye within the orbit. These measurements and the methodology used will contribute to the development of finite element models of the orbit and eye for computational modeling purposes and may be useful in the design of eye protection equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 28 publications
6
70
0
1
Order By: Relevance
“…In the present study we have found that the orbital height, width, orbital index, biorbital-interorbital widths were higher in males than in females. According to the study of Weaver et al [10], similarly to our study, the orbital width and height in males were found to be higher than in females. Furthermore, Husmann et al [2] in their study found that the orbital index is higher in females.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study we have found that the orbital height, width, orbital index, biorbital-interorbital widths were higher in males than in females. According to the study of Weaver et al [10], similarly to our study, the orbital width and height in males were found to be higher than in females. Furthermore, Husmann et al [2] in their study found that the orbital index is higher in females.…”
Section: Discussionsupporting
confidence: 88%
“…Orbits have been used in race and gender prediction of individuals for more than a century [10]. Understanding human anatomy, proportions, mechanical functions and racial variations concerning the ocular anatomy are of vital importance when treating or clinically evaluating patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, titanium-, glass-or ceramicbased enclosures have been the primary means for hermetic sealing in long-term implants, since these hard materials have been shown to be biocompatible and impermeable to water [181]. Even though such hard enclosures are used in the majority of long-term implants [6], [111], [122], [150]- [155], [159], [183], their very large volume and weight, typically much larger than the ICs and supporting components they contain, prohibits their use in high-dimensional neural interfaces heavily constrained by anatomical space such as retinal prostheses [184] and ECoG arrays [30]. In addition, hard packaging requires intricate methods for hermetic sealing of feedthroughs to polymer insulated extensions of the implant such as electrode array cabling, limiting the density of electrode channels due to feedthrough channel spacing requirements.…”
Section: Hermetic Encapsulationmentioning
confidence: 99%
“…3D analysis requires to develop the specific approach to measurement technique and methods (Weaver, 2010, Kim,2015.…”
Section: Introductionmentioning
confidence: 99%